Feasibility and safety of intact cord resuscitation in newborn infants with congenital diaphragmatic hernia (CDH). (November 2017) - Lefebvre, Caroline; Rakza, Thameur; Weslinck, Nathalie; Vaast, Pascal; Houfflin-debarge, Véronique; Mur, Sébastien; Storme, Laurent; ,
Abstract: Background: Starting resuscitation before clamping the umbilical cord at birth may progressively increase pulmonary blood flow while umbilical venous blood flow is still contributing to maintenance of oxygenation and left ventricle preload. Objective: To evaluate the feasibility, safety, and effects of intact cord resuscitation (ICR) on cardiorespiratory adaptation at birth in newborn infants with CDH. Study design: Prospective, observational, single-center pilot study. Methods: Physiologic variables and outcomes were collected prospectively in 40 consecutive newborn infants with an antenatal diagnosis of isolated CDH. Results: Infants were managed with immediate cord clamping (ICC group) from 1/2012 to 5/2014 or the cord was clamped after initiation of resuscitation maneuvers (ICR group) from 6/2014 to 4/2016 (20 in each group). Ante- and postnatal markers of CDH severity were similar between groups. Resuscitation before cord clamping was possible for all infants in the ICR group. No increase in maternal or neonatal adverse events was observed during the period of ICR. The pH was higher and the plasma lactate concentration was significantly lower at one hour after birth in the ICR than in the ICC group (pH = 7.17 ± 0.1 vs 7.08 ± 0.2; lactate = 3.6 ± 2.3 vs 6.6 ± 4.3 mmol/l, p < 0.05). Mean blood pressure was significantly higher in the ICR than in the ICC group at H1 (52 ± 7.7 vs 42 ± 7.5 mmHg), H6 (47 ± 3.9 vs 40 ± 5.6 mmHg) and H12 (44 ± 2.9 vs 39 ± 3.3 mmHg) (p < 0.05). Conclusion: Commencing resuscitation and initiating ventilation while the infant is still attached to the placenta is feasible in infants with CDH. The procedure may support the cardiorespiratory transition at birth in infants with CDH.